The Efek Penambahan Latihan Penguatan dengan Resistance Band terhadap Kekuatan Otot Quadriceps Femoris pada Lansia yang Mendapat Latihan Keseimbangan - Kurniawan, Andriaz; Ambarwati, Endang; Setiawati, Erna (Medica Hospitalia : Journal of Clinical Medicine, 2022)
Abstract Background : Decreased muscle strength and balance disorders that occur in elderly are risk factors for falls. The quadriceps femoris muscle is a predictor of falls and one of the determinants of functional ability in activities of daily living. Balance exercise is one of the exercises to improve the balance of the elderly. Strengthening exercises with resistance bands provide resistance using a stretched elastic band. The objectives of this study was to determine the effect of additional strengthening exercises using resistance bands on increasing the strength of the quadriceps femoris muscle in the elderly who received balance training. Methods: This study is a randomized experimental design with pre and post test design. The subjects were elderly, aged 60-70 years. Subjects were divided into two groups, control group (n=12) and intervention group (n=12). The intervention groups were given balance training 3 times per week for 5 weeks and added strengthening exercises using resistance bands 3 times per week for 5 weeks. The control group only did balance training. Before and after treatment, the strength of the quadriceps femoris muscle was measured in both groups. Results: Statistically significant differences were obtained for right quadriceps femoris muscle strength (p=0.001) and left quadriceps femoris muscle strength (p=0.001) pre and post treatment in the intervention group. In the comparison between groups, there were an increase in the mean muscle strength of the right and left quadriceps femoris, but there were no statistically significant differences in the right quadriceps femoris muscle strength (p=0.088) and left quadriceps femoris muscle strength (p = 0.093). Conclusion: The addition of a resistance band to balance training for 5 weeks had a clinical effect on the quadriceps femoris muscles strength in the elderly but had no statistically significant differences. Keywords: Resistance band, balance training, quadriceps femoris, elderly